1992
DOI: 10.1017/s095026880004958x
|View full text |Cite
|
Sign up to set email alerts
|

Class-specific antibodies to bovine respiratory syncytial virus in experimentally infected lambs

Abstract: SUMMARYEnzyme-linked immunoabsorbent assay (ELISA) was used to titrate virusspecific IgG, IgM and IgA levels in nasal secretions, lung lavage fluids and serum samples sequentially obtained from lambs experimentally infected with bovine respiratory syncytial virus (RSV). Virus-specific IgG and IgM responses were measured by the indirect double antibody sandwich ELISA using anti-bovine RSV monoclonal antibody, as capture antibody, and peroxidase-conjugated antisheep IgG and anti-sheep IgM. Virus-specific IgA ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Since rHRSV is a live virus (17), rHRSV immunization can be regarded as a mild HRSV infection, and challenge with wtHRSV can be regarded as a boosting reinfection. A booster effect in previously immunized individuals becomes apparent by the quick and steep increase of the antibody titer during the recall immune response to infection within 5 to 7 days, as shown in our cotton rat studies (our unpublished data), lambs (42), young children (43), and aged humans (31). The early booster effect was significantly lower in old animals, and this was most pronounced for the increase in the level of neutralizing antibodies, rather than the boost of IgG, indicating that aged individuals are less capable of mounting recall responses of functional antibodies to HRSV.…”
Section: Fig 3 Rhrsv Vaccine-induced Serum Igg Cotton Rats At the Agsupporting
confidence: 61%
“…Since rHRSV is a live virus (17), rHRSV immunization can be regarded as a mild HRSV infection, and challenge with wtHRSV can be regarded as a boosting reinfection. A booster effect in previously immunized individuals becomes apparent by the quick and steep increase of the antibody titer during the recall immune response to infection within 5 to 7 days, as shown in our cotton rat studies (our unpublished data), lambs (42), young children (43), and aged humans (31). The early booster effect was significantly lower in old animals, and this was most pronounced for the increase in the level of neutralizing antibodies, rather than the boost of IgG, indicating that aged individuals are less capable of mounting recall responses of functional antibodies to HRSV.…”
Section: Fig 3 Rhrsv Vaccine-induced Serum Igg Cotton Rats At the Agsupporting
confidence: 61%
“…48 An ELISA was used to titrate virus-specific IgG, IgM, and IgA levels in nasal secretions, lung lavage fluids, and serum samples PI. Mild clinical signs of respiratory disease, BRSV seroconversion, and positive virus isolation attempts indicated that successful experimental infection had occurred.…”
Section: Indicatedmentioning
confidence: 99%